The Interleukin-1 Balance During Encephalitis Is Associated With Clinical Severity, Blood-Brain Barrier Permeability, Neuroimaging Changes, and Disease Outcome - Michael, Benedict Daniel (J Infect Dis, 2016)
Background. Encephalitis is parenchymal brain inflammation, commonly due to herpes simplex virus (HSV). Key host inflammatory mediators and their relationship to blood-brain barrier (BBB) permeability, neuroimaging changes, and disease outcome are poorly understood. Methods. We measured levels of 38 mediators in serum (n = 78) and cerebrospinal fluid (n = 37) specimens from patients with encephalitis, including 17 with disease due to HSV infection. Outcome measures were Glasgow coma and outcome scores; CSF to serum albumin ratio, reflecting BBB permeability; and, in patients with HSV infection, magnetic resonance imaging–based temporal lobe volume. Results. Serum interleukin 1 receptor antagonist (IL-1RA) levels were elevated in patients with a good outcome (P = .004). Among patients infected with HSV, the ratio of CSF IL-1β to IL-1RA was associated with a worse outcome (P = .009); a ratio of ≥0.55 pg/mL had high specificity and sensitivity for a poor outcome (100% and 83%; P = .015). Temporal lobe volume had a negative correlation with serum IL-1RA level (P = .012) and a positive correlation with serum IL-1α level (P = .0003) and CSF IL-1β level (P = .007). A normal coma score was associated with an elevated interleukin 10 (IL-10) level in serum specimens from HSV-infected patients (P = .007) and CSF specimens from all patients (P = .016); the IL-10 level correlated inversely with BBB permeability (P = .005). Conclusions. A proinflammatory cytokine response is associated with greater clinical severity, BBB permeability, and neuroimaging damage during encephalitis. IL-1 antagonists should be investigated as adjunctive treatment in encephalitis.